Assessment of the Ultrasonic Machine for Surface Finishing of 3D-Printed Cobalt-Chromium Alloy by Selective Laser Melting Technology - Mahmood Abdulla Ahmad; Israa Mohammed Hummudi (Journal of Techniques)
The selective laser melting (SLM) system reaches the status of a contender with the traditional casting of dental alloys, with the essential drawback that it is conducive to roughness, making surfaces difficult to finish by the conventional method. Ultrasonic machines (USM) are instrumentally sensible for processes involving metal surface adjustments.